Analysis of the Trash Hero World Movement as a Global Civil Society (GCS) - Asuamah Adade-Yeboah; Marziyeh Farivar (Tinta Emas Publisher, 2025)
Trash Hero World or THW is a GCS that discusses the problem of waste which is one of the main problems that occur in big cities around the world. The purpose of this study is to describe the movement made by Trash Hero World as a Global Civil Society (GCS) in developing organizational networks around the world and overcoming waste problems in the world. The research method used is descriptive. Data collection techniques using documentation studies. The result of this research is that THW is able to become a movement that can be adopted by the international community, because THW uses a strategy from global civil society so that the goals championed by THW can be seen and heard. The results of the research obtained are in the form of THW developing a network of organizations to the world and overcoming waste problems in the world, namely: (1) by mobilizing the public by conducting campaigns and other means in a wider scope, (2) helping to voice the voice of the people who are not represented in making policies, and (3) advocacy for environmental justice. THW also provides various programs to support campaigns and advocacy such as clean action, use of refillable drinking bottles, and reusable bags.